Momigliano and antiquarianism foundations of the modern cultural sciences - Miller, Peter N. 1964- (Univ. of Toronto Press, 2007)
One of the greatest historians of the twentieth century, Arnaldo Momigliano (1908-1987) is known for his path-breaking studies of ancient Greek and Roman history. The encyclopedic knowledge of the ancient world that Momigliano brought to his work, however, enabled him to make connections between ancient history and the subsequent study of that history. His sweeping vision stretched from antiquity to the present day. In Momigliano and Antiquarianism, Peter N. Miller brings together an international and interdisciplinary group of scholars to provide the first serious study of Momigliano's history of historical scholarship. At its core, this collection is devoted to one of Momigliano's most celebrated subjects, the history of antiquarianism, and one of his most audacious claims, that the decay of early modern antiquarianism actually gave birth to the modern cultural sciences - history, sociology, anthropology, art history, archaeology, and history of religion. Filling a gap in the scholarship, this erudite collection will prove fascinating to teachers and students of classics, history, and the human sciences.